2014
DOI: 10.12998/wjcc.v2.i12.873
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic chronic rhinosinusitis in East Asians

Abstract: Chronic rhinosinusitis (CRS) is a common disease worldwide, with a prevalence rate of 5%-15% in the general population. CRS is currently classified into two types: CRS with and without nasal polyps. CRS may also be divided into eosinophilic CRS (ECRS) and non-ECRS subtypes based on the presence of tissue eosinophilic infiltration or not. There are significant geographic and ethnic differences in the tissue eosinophilic infiltration, which is predominant in Western white patients and less common in East Asians,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 76 publications
5
67
2
Order By: Relevance
“…1a). When the levels of IFN-γ were compared between patients with NE-NP and E-NP, as reported previously, 23 the NE-NP patients showed higher levels of IFN-γ ( Fig. 1a).…”
Section: Resultssupporting
confidence: 79%
“…1a). When the levels of IFN-γ were compared between patients with NE-NP and E-NP, as reported previously, 23 the NE-NP patients showed higher levels of IFN-γ ( Fig. 1a).…”
Section: Resultssupporting
confidence: 79%
“…Nasal polyp tissues removed from CRS patients during surgery in Asian countries, including China, Korea, and Japan, have fewer eosinophils than tissues from CRS patients collected in Europe and the United States (reviewed in 156). However, Kim et al (157) studied two similar groups of 230 patients in Korea, one in 1993–1994 and another in 2010–2011, and found that the eosinophil counts rose from 6.8 per high-powered field to 19.3 during this time.…”
Section: Race Eosinophilia and Crs: What Are The Roles Of Genes Andmentioning
confidence: 99%
“…However, Kim et al (157) studied two similar groups of 230 patients in Korea, one in 1993–1994 and another in 2010–2011, and found that the eosinophil counts rose from 6.8 per high-powered field to 19.3 during this time. In general, less than 50% of polyps in Asian countries are eosinophilic, whereas approximately 75% of polyps in Europe and the United States are eosinophilic (149, 156, 158, 159). In Japan, the JESREC study found a prevalence of eosinophilic polyps similar to that in Western countries, and several other studies suggest that the degree of eosinophilia in polyps in Japan, China, Malaysia, Korea, etc.…”
Section: Race Eosinophilia and Crs: What Are The Roles Of Genes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asian countries, NP tissues from patients with CRS have fewer eosinophils than do those from patients with CRS in Europe and the United States. 5,6 However, the degree of eosinophilia in NPs has increased in Asia in the past 2 decades. [7][8][9] The geographical differences and changes in histological characteristics of Asian NPs may be related to genetic, nutritional, or environmental factors.…”
Section: Uncinate Processmentioning
confidence: 99%